Precipitation of aluminum nitride in a high strength maraging steel with low nitrogen content - Jeanmaire, G.; Dehmas, M.; Redjaïmia, A.; Puech, S.; Fribourg, G. (Materials characterization, 2014)
In the present work, aluminum nitride (AlN) precipitation was investigated in a X23NiCoCrMoAl13-6-3 maraging steel with low nitrogen content (wt.% N=5.5ppm). A reliable and robust automatic method by scanning electron microscopy observations coupled with energy dispersive X-ray spectroscopy was developed for the quantification of AlN precipitates. The first stage was to identify the solvus temperature and to develop a heat treatment able to dissolve the AlN precipitates. The experimental determination of equilibrium conditions and solvus temperature show good agreement with ThermoCalc® simulation. Then, from this AlN-free state, the cooling rate, isothermal holding time and temperature were the subject of an intensive investigation in the austenite region of this maraging steel. In spite of the high temperatures used during heat treatments, the growth kinetic of the largest AlN precipitates (>1μm) is slow. The cooling rate has a major effect on the size and the number density of AlN due to a higher driving force for nucleation at low temperatures. At last, quenching prior to isothermal annealing at high temperatures leads to fine and dense AlN precipitation, resulting from the martensite to austenite transformation. Experimental results will be discussed and compared with kinetic data obtained with the mobility database MobFe2 implemented in Dictra® software. •Slow dissolution kinetic of AlN precipitates due to both their large size and small chemical driving force•Significant effects of cooling rate prior isothermal heat treatment, holding time and temperature on AlN precipitation•Size of AlN precipitates can be reduced by quenching prior isothermal holding.•Fine precipitation of AlN related to the α→γ transformation